Psychological Adjustment to Acquired Facial Disfigurement: personality characteristics, self-concept and satisfaction with Social Support - a longitudinal study - J. Mendes; R. Rego; T. Moss; D. Alcaidinho (PsychTech & Health Journal)
We intend to contribute towards a better understanding of the variables that affect the Schematic Investment and Self-consciousness of the appearance of those who suffer from acquired facial disfigurement. The sample consisted of 67 individuals who have been submitted to plastic and reconstructive surgery and completed a questionnaire evaluating the influence of personality traits, optimism, self-concept, emotions and perception of satisfaction with social support, and with the perception of appearance during their admittance to the hospital, and 12 months after the surgery. There were meaningful statistical differences in both evaluation moments for the variables Neuroticism, Extraversion, Openness, Agreeableness, Conscientiousness, Optimism, Positive and Negative Affect, Self-Concept, and Social Support Satisfaction. In both evaluations, Self-conscientiousness of Appearance reveals a positive relationship with Neuroticism and negative relation with Self-concept. Results show that Schematic Investment and Self-conscientiousness of appearance vary in time and that there are variants that influence the psychological adjustment to acquired facial disfigurement.